Building sustainable futures for adult learners - Holtz, Jennifer K.; Springer, Stephen B. (Adult learning in professional, organizational, and community settings., 2015)
Building Sustainable Futures for Adult Learners is an edited and refereed collection of papers published in conjunction with the joint Adult Higher Educational Alliance (AHEA) and American Association of Adult and Continuing Education Conferences (AAACE). This book is the third in a series of scholarly publications associated with the annual AHEA conference. The book is arranged thematically according to the topics of submissions. Building Sustainable Futures is important because it fills a unique niche in the field of adult education, extends the scope of AHEA to a larger audience, and offers a current volume for scholars and practitioners based on both research and practice-based research.